1999
DOI: 10.1094/mpmi.1999.12.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Tight Physical Linkage of the Nematode Resistance GeneGpa2and the Virus Resistance GeneRxon a Single Segment Introgressed from the Wild SpeciesSolanum tuberosumsubsp.andigenaCPC 1673 into Cultivated Potato

Abstract: Comparative mapping studies within several plant genera have shown that genes for resistance to taxonomically diverse pathogens are often co-localized on the maps of these genotypes. Here we describe the genetic analysis of such a gene cluster on chromosome 12 of potato. This cluster harbors the resistance loci Gpa2 and Rx, which confer resistance to the potato cyst nematode Globodera pallida and potato virus X (PVX), respectively. By screening two mapping populations with 10 CAPS (cleaved amplified polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 60 publications
0
50
0
1
Order By: Relevance
“…A HindIII BAC-library of the resistant parent (SH83-92-488) was available (Rouppe van der Voort et al 1999). This $11 genome equivalent BAC library comprises almost 98,000 BAC clones with an average insert size of 100 kb.…”
Section: Bac-library and Plasmid Isolationmentioning
confidence: 99%
“…A HindIII BAC-library of the resistant parent (SH83-92-488) was available (Rouppe van der Voort et al 1999). This $11 genome equivalent BAC library comprises almost 98,000 BAC clones with an average insert size of 100 kb.…”
Section: Bac-library and Plasmid Isolationmentioning
confidence: 99%
“…The tetraploid resistant female parent 707TG11-1 was derived from a quadruple hybrid ABPT clone (Hermsen and Ramanna 1973). The diploid susceptible male parent RH89-039-16, producing unreduced 2n pollen, is one of the advanced clones widely used for mapping research at the Laboratory of Plant Breeding and the Laboratory of Nematology, Wageningen University (Rouppe van der Voort et al 1997aVoort et al , b, 1998Voort et al , 1999Huang et al 2004;van Os et al personal communication).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Gpa2, which confers resistance against the potato cyst nematode Globodera pillida, was found to be tightly linked in the potato genome to Rx, which is responsible for resistance against potato virus X (PVX; van der Voort et al, 1999). Their cloning and molecular characterization indicate that they are highly similar at the amino acid level and thus form a single R gene family (Bendahmane et al, 1999; J. Bakker, personal communication).HRT appears to have been formed in part by an unequal crossing over between progenitor genes related to RPP8 Inoculated leaves were stained with trypan blue to show the relative size of necrotic tissue at 3 DPI. RNA isolated from uninoculated (U) leaves at 6 DPI was analyzed for PR-1 induction, systemic spread of TCV, and HRT expression.…”
mentioning
confidence: 99%
“…This HR Ϫ resistance is reminiscent of the extreme resistance exhibited by potatoes carrying Rx after infection with PVX. In Rx-containing potato plants, the rapid arrest of PVX replication in the initially infected cells appears to prevent development of an HR (Kohm et al, 1993;Bendahmane et al, 1999).Analysis of HRT mRNA levels in the transformed lines revealed that the extent of HRT expression directly correlated with the extent of TCV resistance and was inversely proportional to lesion size. Plants of the HR Ϫ but extreme resistant lines expressed three-to fivefold more HRT than did Di-17 plants ( Figure 5), whereas lines exhibiting a micro-HR and partial resistance had intermediate HRT expression.…”
mentioning
confidence: 99%